2011
DOI: 10.4103/0974-9233.90129
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser-assisted cataract surgery: A current review

Abstract: To evaluate the safety, efficacy, advantages, and limitations of femtosecond laser-assisted cataract surgery through a review of the literature. A PubMed search was conducted using topic-appropriate keywords to screen and select articles. Initial research has shown appropriate safety and efficacy of femtosecond laser-assisted cataract surgery, with improvements in anterior capsulotomy, phacofragmentation, and corneal incision. Limitations of these studies include small sample size and short-term follow-up. Cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The recent introduction of femtosecond laser‐assisted cataract surgery (FLACS) has shown promising results (Moshirfar et al. ). This technique combines a high‐resolution anterior segment imaging system with a femtosecond laser (FL), which delivers short pulses (10 −15 seconds) of energy at near‐infrared wavelength, which can be focused at very specific depths within the anterior chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The recent introduction of femtosecond laser‐assisted cataract surgery (FLACS) has shown promising results (Moshirfar et al. ). This technique combines a high‐resolution anterior segment imaging system with a femtosecond laser (FL), which delivers short pulses (10 −15 seconds) of energy at near‐infrared wavelength, which can be focused at very specific depths within the anterior chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several studies have reported that the application of FSL can alleviate corneal endothelial cell loss and corneal edema in the early postoperative period 13 18 19 20 . Another advantage of FLACS is able to create a more circular and precise capsulorrhexis, which can facilitate phacoemulsification and IOL implantation, and offer more accurate refractive outcomes after surgery 21 22 23 24 . However, some researches also suggested FLACS has not provide advantage over conventional CP, and it will not be a standard method for cataract surgery ten years from now 25 .…”
mentioning
confidence: 99%
“…Active uveitis, thick scarred cornea, patients with active movement disorders like Parkinson's disease are still regarded as contraindication for this technology as complete laser penetration and docking are not possible in these cases. 5…”
Section: Sachdev M Et Almentioning
confidence: 99%